The doctor's kidney diets : a nutritional guide to managing and slowing the progression of chronic kidney disease - Kang, Mandip S. (Square One Publishers, 2015)
This book is divided into two parts. Part One provides a clear overview of kidney function, kidney disease, and the role that nutrition plays in the treatment of kidney problems. The doctor then reviews the special dietary considerations of individuals with CKD, including the need to limit certain nutrients, fluids, and other dietary components. Because different patients have different nutritional requirements, the doctor discusses the most commonly prescribed CKD diets--the DASH diet, heart disease and diabetes diets, diets for dialysis, and more--and concludes with important tips for enhancing overall health and maximizing treatment success. Then Part Two offers a wide variety of recipes for dishes that follow the dietary guidelines highlighted in Part One.